Cities, urban and rural: Disagreements and convergences - Barrenechea Lercari, Carlos (1996)
This text is a reflection that seeks to share experiences and visions on the multiple and dynamic relationship between the urban and the rural, and on the weight of the larger cities in the short experience of regionalization, in the space of what we have been calling the Great South. We are interested, in particular, in describing and offering a reading —rather than hiding in rational analysis— of the subjectivity of social actors who, in this as in many other cases and topics, are very important to understand our possibilities, but also our repeated bumps.